Integrasi Ilmu Dan Pendidikan Dalam Islam Surah Al-Mujadillah Ayat 11 - Nopalia Susanti; Elis Setiawati; Sari Wahyuni Siregar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Islam is a religion whose holy book is the Koran and respects people of knowledge and faith. Knowledgeable people will have a positive attitude because of their knowledge and can apply it in everyday life. The purpose of writing this article is to discuss the importance of understanding Surah Al-Mujadillah verse 11 in the Al-Qur'an according to several interpretations. According to some interpretations, humans are commanded to respect other people in meetings. The discussion remains focused on how to gather according to the interests of the ulama, where to achieve higher knowledge, seekers of knowledge must follow the provisions of Allah SWT and must be polite when attending meetings.